Morphology of the equatorial ionization anomaly in Africa and Middle East due to a sudden stratospheric warming event. (March 2019) - Bolaji, O.S.; Oyeyemi, E.O.; Jimoh, O.E.; Fujimoto, A.; Doherty, P.H.; Owolabi, O.P.; Adeniyi, J.O.; Falayi, E.O.; Abe, E.; Kaka, R.O.; Kotoye, A.
Abstract: Using total electron content (TEC) data deduced from 18 Global Positioning System (GPS) receivers in Africa and Middle East, we investigated the morphology of the equatorial ionization anomaly (EIA) and its underlying variations before, during and after the 2009 sudden stratospheric warming (SSW) event. A southern EIA crest stronger than the northern EIA crest was observed for most of the days before the SSW event, while the EIA troughs were significantly obliterated after these SSW induced phases. In addition to the observed marked depletion of the hemispheric EIA crests during the SSW peak phase, we observed a terdiurnal variation straddling the northern EIA crests. This background terdiurnal signature is suggested to be partly responsible for the transport of more plasma to the northern hemisphere at the expense of southern hemisphere during the SSW peak phase. The consequences are higher pre-noon and post noon crests in the northern hemisphere compared to a single crest in the southern hemisphere. Contrary to previous modeling and experimental reports that the reductions in ionospheric TEC are due to semidiurnal variations resulting from the SSW peak phase, our results show that a terdiurnal variation was responsible for reducing the EEJ strength and TEC at the E-region and F2-region's topside, respectively. At the southern middle latitudes, an underlying diurnal variation was seen to initiate an increment in TEC during the SSW descending phase. Highlights: We used 18 GPS station to unveil equatorial ionization anomaly from total electron content (TEC) between January and March, 2009 over Africa and Middle East. For the first time, we used experimental investigation to unveil a terdiurnal variation that initiates northern pre-noon and post noon crests. This terdiurnal variation reduces all of the station TEC values and move more plasma to the northern pre-noon and post noon peak than the southern crest during SSW peak phase.